(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2023)
This research departs from a phenomenon in society, namely the practice of using ducks in Olak Kemang Village, Maro Sebo Ulu District. This is done by people who are less fortunate or cannot afford to buy a goat to slaughter, and this is a tradition in some communities that has become a practice carried out by parents who are less well off to acquit their newborn children. This research aims to find out the basis for using ducks as aqiqah animals, to know the procession of carrying out aqiqah using ducks in Olak Kemang Village, and to find out the understanding of the Olak Kemang community regarding the aqiqah tradition using ducks. This research is qualitative research with a living hadith approach, which uses a phenomenological paradigm. The data collection techniques in this research used documentation, observation, and interviews. The results of this research state that the Olak Kemang people use ducks as religious animals based on the hadith narrated by Ibnu Majah no. 3165; Hadith from Malik; and also the history of Ali bin Abi Talib, namely the aqiqah with chickens. The implementation procession takes the form of; slaughtering ducks, giving names, shaving hair, barzanji marhaban, giving envelopes, and eating offerings. Then society’s understanding is divided into several things; following the Sunnah of the Prophet SAW., an inner bond to good deeds, as a baby’s safety, the baby is protected from Satan’s interference, as a parent’s gratitude, providing intercession for parents, aqiqah vehicle for vehicles in the afterlife.